KONSEP PENDIDIKAN ANAK USIA DINI DALAM KELUARGA DALAM PERSPEKTIF ISLAM DITENGAH-TENGAH PANDEMI COVID-19 - Rizqi, Anggi Maulana; Riyadi, Agus (JURNAL PAUD AGAPEDIA, 2021)
This study will discuss early childhood education in the family during the Covid-19 pandemic. Where family education is recognized as the heart of the educational trilogy in Islamic education. In addition to school education and community education, family education has a very important urgency as an effort to improve the quality of education to carry out. Aimed at forming a generation that has high intellectual and emotional as well as high morality and spirituality. In accordance with its concept, the integrated curriculum balances the thinking process, remembrance process, sports, and the sense of students so as to form a generation that is virtuous, able-bodied, knowledgeable, and free-thinking along with its applied educational methods as direction, training, assignment, habituation, escort, and exemplary of all family members at home. That is the essence of the concept of early childhood education in the family.Penelitian ini akan membahas tentang Pendidikan Anak usia dini dalam Keluarga ditengah-tengah pandemic covid-19. Yang mana pendidikan keluarga merupakan jantung dari trilogi pendidikan yang ada dalam pendidikan islam. Selain pendidikan sekolah dan pendidikan masyarakat, pendidikan keluarga mempunyai urgensi yang sangat penting sebagai upaya peningkatan kualitas pendidikan yang dijalankan. Bertujuan membentuk generasi yang mempunyai intelektualitas dan emosional tinggi juga moralitas dan spiritualitas tinggi. Dalam konsepnya, kurikulum terpadu menyeimbangkan antara olah fikir, olah dzikir, olah raga dan olah rasa peserta didik sehingga terbentuk generasi yang berbudi tinggi, berbadan sehat, berpengetahuan luas dan berfikiran bebas dengan metode pendidikan yang diterapkannya yaitu pengarahan, pelatihan, penugasan, pembiasaan, pengawalan dan keteladan dari semua anggota keluarga yang ada di rumah. Itulah hakikat dari konsep pendidikan anak usia dini dalam keluarga.